In Silico and Experimental Analyses of Long Non-coding RNA TMPO-AS1 Expression in Iranian Patients with Gastric Cancer. - Mohammadali, Elaheh; Safaralizadeh, Reza; Poursheikhani, Arash; Asvadi, Tooraj; Teimourian, Shahram; Baradaran, Behzad (International Journal of Cancer Management, 2023)
Background: In recent decades, many long non-coding RNAs (lncRNAs) have been reported to play a prominent role in tumorigenesis and the progression of human cancers, including gastric cancer (GC), a leading cause of cancer death in Iranian men and women. Studies have demonstrated that thymopoietin antisense transcript 1 (TMPO-AS1) was upregulated indifferent cancers by acting as an oncogenic lncRNA. Objectives: This study aimed to evaluate the expression of lncRNA TMPO-AS1 in Iranian patients with GC. Methods: In order to conduct the present study, 40 gastric tumor samples and 40 marginal noncancerous counterparts were collected. The characteristics of patients' samples were recorded, and the TMPO-AS1 expression levels were evaluated by qRT-PCR analysis. The Cancer Genome Atlas (TCGA) data for TMPO-AS1 were used and analyzed through GEPIA and TANRIC online tools. Receiver operating characteristic (ROC) curve analysis was used to estimate the diagnostic value. Student t-test, one-way ANOVA, and chi-square test were accomplished via SPSS software. Results: Our data demonstrated that TMPO-AS1 was overexpressed in cancerous tissues compared to adjacent nonmalignant ones (P = 0.0076). None of the demographic and clinicopathological data were associated with TMPO-ASl expression levels. The TCGA data demonstrated that TMPO-AS1 was upregulated in GC tissues in comparison to adjacent nonmalignant ones (P = 0.001). ROC curve analysis suggested that TMPO-AS1 expression levels could discriminate GC tumor tissues from normal ones (AUC = 0.699, P = 0.001). Conclusions: Altogether, in our study, we demonstrated that lncRNA TMPO-AS1 maybe considered a biomarker in Iranian patients with GC. However, further investigations are required to confirm the potential application of this lncRNA in diagnosis, prognosis, and therapeutic applications of GC.